Penyuluhan Bahaya Merokok Bagi Kesehatan Pada Siswa-Siswi SMA Muhammadiyah 1 Kota Pekanbaru - Neni Ristiani; Mahendra Mahendra; Evy Eryta (Jurnal Pengabdian Bidang Kesehatan, 2024)
Adolescence is a phase that is very susceptible to influence from the social environment, both positive and negative. It is not uncommon for teenagers to fall into an unhealthy lifestyle that is dangerous to their health and safety. One of the bad influences that can occur in adolescence is the habit of smoking. Smoking is one of the causes of quite a lot of health problems. The urgency of counseling or health education for teenagers about the dangers and risks of smoking for health aims to ensure that the nation's future generations do not fall into habits that can damage their future.